The Effect of Mutualism, Trust and Commitment on MSME Development With Attitude Variable to The Covid-19 Pandemic as a Moderation Variable - Eni Puji Estuti; Zumrotun Nafiah; Eko Sasono (Universitas Negeri Semarang, 2023)
In the increasingly rapid development of the information age, MSME actors are required to optimize resources, but with limited capital and so on, MSME actors do not fully have all the resources needed. Coopetition is one of the phenomena currently being carried out by business actors and MSMEs. Where in coopetition the two parties who compete with each other at the same time also decide to work together. This study aims to analyze 3 dimensions of coopetition, namely mutualism, trust and commitment to the development of MSMEs by involving attitudes towards pandemics as a moderating variable. This research is a quantitative study with a population of business actors (MSMEs) who are in the Semarang City BUMN House which has as many as 2,000 MSME members. The test uses multiple linear regression analysis and Moderated Regression Analysis (MRA). The results of the analysis show that mutualism, trust and commitment each have an effect on the development of MSMEs. Attitudes towards the Covid-19 pandemic did not work as a moderating variable.